Analysis of Countermeasures Against Access Driven Cache Attacks on AES - Blömer, Johannes; Krummel, Volker (Selected Areas in Cryptography)

Cryptanalysis of Unbalanced RSA with Small CRT-Exponent - May, Alexander (Advances in Cryptology — CRYPTO 2002)

Low Secret Exponent RSA Revisited - Blömer, Johannes; May, Alexander (Lecture Notes in Computer Science)

Key Revocation with Interval Cover Families - Blömer, Johannes; May, Alexander (Selected Areas in Cryptography)

Dimension Reduction Methods for Convolution Modular Lattices - May, Alexander; Silverman, Joseph H. (Lecture Notes in Computer Science)

A Probabilistic Zero-Test for Expressions Involving Roots of Rational Numbers - Blömer, Johannes (Algorithms — ESA’ 98)

Approximierbarkeit durch konstante Stichproben unter Berücksichtigung verschiedener Divergenz- und Ähnlichkeitsmaße beim k-Clustering-Problem - Ziegert, Steffen

Sichere Kryptosysteme durch Zero-Knowledge - Richert, Manuel

Angriffe auf RSA-Varianten bei partiell bekannten geheimen Schlüsseln - Klein, Wiebke
Keywords: Diplomarbeit

Kryptanalyse des EAC-Protokolls biometrischer Reisepässe - Käthler, Olga
Keywords: Diplomarbeit

Analyse von verallgemeinerten RSA Polynomen mit Hilfe der Coppersmithschen Methode - Brieden, Benedikt
Keywords: Diplomarbeit

Untersuchung von Clusteringalgorithmen für die Kullback-Leibler Divergenz - Kuntze, Daniel
Keywords: Diplomarbeit

Vergleich multivariater Varianten der Methode von Coppersmith - Borghoff, Julia
Keywords: Diplomarbeit

Untersuchungen zur Sicherheit einzelner RSA Bits - Landwehr, Andreas Cord

Ein erschöpfende Suche vermeidender Algorithmus für allgemeines k-SAT - Klose, Jaroslaw

Reduktionen von CVP mit wenigen Lösungen auf CVP mit eindeutigen Lösungen - Niemeier, Martin

Behandlung von Korrekturtermen in der Methode von Coppersmith - Birkner, Stefan

Randomness and Secrecy - A Brief Introduction - Blömer, Johannes (Journal of Universal Computer Science (J.UCS))
We give a brief introduction to probabilistic encryptions. This serves as an example how randomness plays a pivotal role in cryptographic systems that satisfy advanced security concepts.

Fault Based Collision Attacks on AES - Blömer, Johannes; Krummel, Volker (Lecture Notes in Computer Science)

Wagner’s Attack on a Secure CRT-RSA Algorithm Reconsidered - Blömer, Johannes; Otto, Martin (Lecture Notes in Computer Science)

Sign Change Fault Attacks on Elliptic Curve Cryptosystems - Blömer, Johannes; Otto, Martin; Seifert, Jean-Pierre (Lecture Notes in Computer Science)

Implementierung und Simulation von Cache-Angriffen auf AES - Funke, Rafael

Von identitätsbasierten Kryptosystemen zu CCA-Sicherheit - Schrieb, Jonas

Samplemethoden in der algorithmischen Geometrie der Zahlen - Naewe, Stefanie
Keywords: Diplomarbeit

Boomerang- und Rechteckangriff auf AES - Gorski, Michael
Keywords: Diplomarbeit

Fault Attacks and Countermeasures - Otto, Martin

A Tool Kit for Finding Small Roots of Bivariate Polynomials over the Integers - Blömer, Johannes; May, Alexander (EUROCRYPT 2005)

Partial Key Exposure Attacks on RSA up to Full Size Exponents - Ernst, Matthias; Jochemsz, Ellen; May, Alexander; de Weger, Benne (EUROCRYPT 2005)

Implementierung von wichtigen Teilen des Schoof-Elkies-Atkin Algorithmus zum Bestimmen der Punktanzahl einer elliptischen Kurve - Hornkamp, Christian

Laufzeitanalyse- und vergleich verschiedener Algorithmen zur schnellen skalaren Multiplikation auf elliptischen Kurven - Süß, Tim

Analyse von RSA mittels Coppersmith Methode - Ernst, Matthias
Keywords: Diplomarbeit

Implementierung der Coppersmith-Methode zur Untersuchung von Schwachstellen bei RSA - Spanke, Christoph
Keywords: Diplomarbeit

Provably Secure Masking of AES - Blömer, Johannes; Guajardo, Jorge; Krummel, Volker (Selected Areas in Cryptography)

A Generalized Wiener Attack on RSA - Blömer, Johannes; May, Alexander (Public Key Cryptography – PKC 2004)

Secret Exponent Attacks on RSA-type Schemes with Moduli N=p^{r}q - May, Alexander (Public Key Cryptography – PKC 2004)

Computing the RSA Secret Key Is Deterministic Polynomial Time Equivalent to Factoring - May, Alexander (Advances in Cryptology – CRYPTO 2004)

A new CRT-RSA algorithm secure against bellcore attacks - Blömer, Johannes; Otto, Martin; Seifert, Jean-Pierre (Proceedings of the 10th ACM conference on Computer and communication security - CCS '03)

Neue Schranken für die Coppersmith-Methode über den ganzen Zahlen - Dumrauf, Dominic

Implementierung und Evaluierung eines Angriffs auf DSA - Herden, Tim

Implementierung eines Verfahrens zur Berechnung optimaler längenbeschränkter Präfix-Codes - Gesemann, Sebastian

Implementierung und Evaluation einiger Algorithmen für Kryptosysteme auf elliptischen Kurven - Gorski, Michael

New RSA Vulnerabilities Using Lattice Reduction Methods - May, Alexander

New Partial Key Exposure Attacks on RSA - Blömer, Johannes; May, Alexander (Advances in Cryptology - CRYPTO 2003)

Fault Based Cryptanalysis of the Advanced Encryption Standard (AES) - Blömer, Johannes; Seifert, Jean-Pierre (Financial Cryptography)

Asymptotische Optimalität von LZ77 bei beschränktem Speicher - Ernst, Matthias

Asymptotische Optimalität von Lempel-Ziv bei Markowprozessen - Voß, Kerstin

Markovprozesse zur Modellierung bei Codekompression - Hoppe, Ulrich
Keywords: Diplomarbeit

Implementierung eines arithmetischen Dekodierers in Java - Unterkirchner, Claudia

Tabellenbasierte arithmetische Codierung - Kuntze, Daniel

Kompressionsverlust bei arithmetischer Codierung mit endlicher Präzision - Soltenborn, Christian

Implementierung eines arithmetischen Kodierers in Java - Todtenbier, Christian

Fehlerangriffe auf spezielle Implementierungen von RSA - Ziegler, Max

Verkürzte Huffman-Codierung zur Codekompression - Lindner, Marvin

Tabellenbasierte arithmetische Kodierung bei allgemeinen Alphabeten - Ackermann, Marcel R.
Keywords: Diplomarbeit

Priority encoding transmission - Albanese, Andres; Blömer, Johannes; Edmonds, Jeff; Luby, Michael; Sudan, Madhu (IEEE Transactions on Information Theory)

Priority encoding transmission - Albanese, A.; Blömer, Johannes; Edmonds, J.; Luby, M.; Sudan, M. (Proceedings 35th Annual Symposium on Foundations of Computer Science)

Computing sums of radicals in polynomial time - Blömer, Johannes ([1991] Proceedings 32nd Annual Symposium of Foundations of Computer Science)

Denesting by Bounded Degree Radicals - Blömer, J. (Algorithmica)
Keywords: Applied Mathematics; Computer Science Applications; General Computer Science

Construction of Pseudorandom Functions - Fricke, Birgitta
Keywords: Diplomarbeit

Evaluierung und Implementierung eines vollständig verteilten RSA-Kryptographiesystems - Deveci, Deniz
Keywords: Diplomarbeit

The Weil-Pairing and Signature Schemes in Elliptic Curve Cryptography - Helbich, Anke
Keywords: Diplomarbeit

Timing Attacks for Cryptosystems based on Elliptic Curves - Schepers, Daniel
Keywords: Diplomarbeit

Implementierung und Evaluation eines MDS-Blockcodes mit unabhängigen Paritätssymbolen - Hoppe, Ulrich

Sicherheit und Anwendungen des Advanced Encryption Standard (AES) Rijndael - Krummel, Volker
Keywords: Diplomarbeit

Brauer Addition-Subtraction Chains - Otto, Martin
Keywords: Diplomarbeit

Closest Vectors, Successive Minima, and Dual HKZ-Bases of Lattices - Blömer, Johannes (Automata, Languages and Programming)

On the complexity of computing short linearly independent vectors and short bases in a lattice - Blömer, Johannes; Seifert, Jean-Pierre (Proceedings of the thirty-first annual ACM symposium on Theory of computing - STOC '99)

A lower bound for a class of graph based loss resilient codes - Blömer, Johannes; Trachsler, Beat (Technical report/Departement of Computer Science, ETH Zürich)

Denesting by bounded degree radicals - Blömer, Johannes (Algorithms — ESA '97)

The rank of sparse random matrices over finite fields - Blömer, Johannes; Karp, Richard; Welzl, Emo (Random Structures & Algorithms)
Keywords: random matrices; rank; finite fields

Approximate matching of polygonal shapes - Alt, Helmut; Behrends, Bernd; Blömer, Johannes (Annals of Mathematics and Artificial Intelligence)
For two given simple polygonsP, Q, the problem is to determine a rigid motionI ofQ giving the best possible match betweenP andQ, i.e. minimizing the Hausdorff distance betweenP andI(Q). Faster algorithms as the one for the general problem are obtained for special cases, namely thatI is restricted to translations or even to translations only in one specified direction. It turns out that determining pseudo-optimal solutions, i.e. ones that differ from the optimum by just a constant factor, can be done much more efficiently than determining optimal solutions. In the most general case, the algorithm for the pseudo-optimal solution is based on the surprising fact that for the optimal possible match betweenP and an imageI(Q) ofQ, the distance between the centroids of the edges of the convex hulls ofP andI(Q) is a constant multiple of the Hausdorff distance betweenP andI(Q). It is also shown that the Hausdorff distance between two polygons can be determined in timeO(n logn), wheren is the total number of vertices.

An XOR-based erasure-resilient coding scheme - Blömer, Johannes; Kalfane, Malik; Karp, Richard; Karpinski, Marek; Luby, Michael; Zuckerman, David

On Kummer theory and the number of roots of unity in radical extensions of Q - Blömer, Johannes

Simplifying Expressions Involving Radicals - Blömer, Johannes

Resemblance and symmetries of geometric patterns - Alt, Helmut; Blömer, Johannes (Data structures and efficient algorithms)

How to denest Ramanujan's nested radicals - Blömer, Johannes (Proceedings., 33rd Annual Symposium on Foundations of Computer Science)

Approximate matching of polygonal shapes (extended abstract) - Alt, Helmut; Behrends, Bernd; Blömer, Johannes (Proceedings of the seventh annual symposium on Computational geometry - SCG '91)

Computing sums of radicals in polynomial time - Blömer, Johannes (Proceedings 32nd Annual Symposium of Foundations of Computer Science)

Approximation of convex polygons - Alt, Helmut; Blömer, Johannes; Wagener, Hubert (Automata, Languages and Programming)